MODIFYING A MONOPOLY GAME FOR TEACHING WRITTEN VOCABULARY FOR THE SEVENTH GRADERS OF TERANG BANGSA JUNIOR HIGH SCHOOL (English Education Journal, 2014)
This study is aimed at describing the existing media for learning vocabulary at Terang Bangsa Junior High School, to describe sort of English materials that are needed by seventh graders learners which do not exist at Terang Bangsa Junior High School, to explain modifying a Gladden Monopoly game for learning vocabulary to the seventh graders, and to explain the effectiveness of Gladden Monopoly game for teaching vocabulary to the  seventh graders. This study used a Research & Development (R&D) design, which was used to modify products and measure the effectiveness of the development proposed by Borg and Gall (2007).  The results of the study showed that English teaching material by using Gladden Monopoly game was effective in improving students’ achievement of vocabulary learning. Those were supported by the results of pre and post-test. Based on the results of the observation checklist, questionnaire, and the experts’ validation it showed that Gladden Monopoly game helped in studying English. It can be seen from the result of the answers of the questionnaires in which more than 75% of the students answered ‘A’ or ‘B’ that indicates that the product was easy and attractive to use.